ANALISIS PERKEMBANGAN EKONOMI SYARIAH DI INDONESIA TERHADAP STABILITAS SISTEM KEUANGAN NASIONAL - Efrizal Rizqia Akbar (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the development of the Islamic economy in Indonesia and its contribution to the stability of the national financial system. The method used is library research with a descriptive qualitative approach through literature reviews from scientific journals, reports published by Bank Indonesia (BI), the Financial Services Authority (OJK), and other related academic publications. The results of the study indicate that the Islamic economy in Indonesia has experienced significant growth, marked by the increase in Islamic banking assets, the development of sukuk, and the improvement of Islamic financial literacy. In addition, the Islamic economy contributes to financial system stability through its interest-free principles, real-sector-based transactions, and profit-and-loss sharing system, which is considered more moderate toward financial risks. Therefore, the Islamic economy plays an important role in supporting the stability of the national financial system amid global economic dynamics.